Family, society and the individual: determinants of entrepreneurial attitudes among youth in Chennai, South India - Jagannathan, Radha; Tosun, Jale (Journal of Global Entrepreneurship Research, 2017)
High rates of youth unemployment across the world have captured the attention of many world organizations and other policy makers. One policy solution that has been proposed to curb these high rates is encouraging youth entrepreneurship. In this paper, we examine the formation of attitudes that are favorable to entrepreneurship using data from 185 business students in South India. We adopt an approach that tests the relative efficacy of two principal factors in the formation of entrepreneurial attitude, i.e., stocks of youth human/social capital and a series of personality traits. Results from a probit model suggest that the youth’s prior labor market experience, the social capital that youth have accumulated through volunteering, and the social connections that parents have made are all highly predictive of pro-entrepreneurial attitudes; personality traits exert less importance. Implications for these findings are discussed for the creation of strategies that can stimulate entrepreneurship among youth as one way to combat high rates of youth unemployment.